‘Campus, Home, City: Laboratories of Change’, the Education or Sustainability Program of the University of a Coruña - Soto, Manuel; Marcote, Pedro Vega; Dopico, Domingo Calvo; Torrijos, Verónica; Dono, Martina (Journal of Sustainability Perspectives, 2023)
The program 'Campus, home, city: laboratories of change', aims to promote the students and citizenship formation in the basic concepts of environmental and social sustainability, responding to the priority challenges for our society such as climate change, waste production, circular economy or sustainable mobility. The proposed service-learning, hands-on activities takes advantage of the housing, the university and the city as places for researching and experimentation. A feature of this program is the use of online ICT tools for fieldwork, in particular the survey and mapping of waste generation and footprint, water use efficiency, transport footprint and consumption of energy. The project has the collaboration of the Alcoa Foundation and is now in its 6th Edition, adding up the participation of more than 11,000 people. In the last two editions, the project has been extended to primary, secondary and vocational training centers in the region of A Mariña.